Reassessment of failed beta-blocker treatment in angina pectoris by peak-exercise heart rate measurements. Issue 5984 (13th September 1975) - Jackson, G; Atkinson, L; Oram, S
Abstract : Twenty-one patients with angina pectoris were treated with adrenergic beta-receptor antagonists. Previously the resting heart rate had been used as a guide to treatment, a reduction in the rate to 55-60 beats/min without symptomatic improvement indicating failure of medical treatment. These patients were re-evaluated before coronary arteriography using the peak-exercise heart rate as an index of adrenergic beta-receptor antagonism. The dose of beta-blocking drugs was increased to produce a peak-exercise heart rate of less than 100 beats/min or a consistent rate of 100-125 beats/min which would not lessen in spite of progressive dose increments. The resting heart rate was ignored. On these criteria 15 patients previously considered to have responded inadequately to beta-blockade responded satisfactorily and were therefore removed from the waiting list for coronary arteriography. They all remained well up to two years later. Six patients failed to respond and had coronary arteriography with a view to surgical treatment. Reliance on the resting heart rate as the index of optimum adrenergic beta-receptor antagonism is likely to lead to premature or unnecessary referral for surgery; the failure of beta-blockade in the treatment of angina pectoris can be determined simply and accurately by using peak-exercise heart rate.